Development of Project-Based Science Learning Materials Using A Culturally Responsive Teaching Approach to Enhance Collaboration Skills and Conceptual Understanding - Sakinah, Nur Milatis; Sudarmin, Sudarmin; Saptono, Sigit (Universitas Negeri Semarang, 2025)
This study aims to describe the characteristics of project-based science learning materials developed using the Culturally Responsive Teaching (CRT) approach and to analyze their feasibility and effectiveness. The research employed a Research and Development (R&D) design with the ADDIE model, consisting of five stages: Analyze, Design, Development, Implementation, and Evaluation. The developed product comprised a set of science learning materials for Grade VII on the topic of Motion and Force, integrating local cultural contexts into every stage of the project-based learning process. The resulting materials included a teaching module, student worksheets, and supplementary resources designed to be contextual, communicative, and aligned with the Merdeka Curriculum. Expert validation indicated that the materials were highly feasible in terms of content, language, visual presentation, and integration of local cultural values. Practicality testing revealed that both teachers and students considered the materials easy to use, engaging, and relevant to their real-life experiences. Effectiveness testing through a post-test design demonstrated a significant improvement in students’ conceptual understanding of science, as well as enhanced motivation and collaborative skills. In conclusion, the project-based science learning materials developed with the CRT approach are considered feasible, practical, and effective, particularly in fostering contextual and inclusive learning for Grade VII students.